PENGARUH FASILITAS DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA PELABUHAN BATU AMPAR DI BATAM - NELSI DALAME; TRIANA ANANDA RUSTAM (JURNAL ILMIAH KOHESI, 2020)
The development of the business world is currently experiencing a very rapid increase both engaged in manufacturing andservices. Customer satisfaction is the key in creating customer loyalty. To achieve customer satisfaction the company mustprovide good facilities and also describe good service quality so that it can create customer satisfaction. The purpose of thisstudy is to examine and analyze the effect of facilities and service quality on customer satisfaction. This research wasconducted at Batam's Batu Ampar Harbor. Data collection techniques using non-probability random sampling., And datacollection techniques using survey methods through questionnaires. Calculation of the number of samples can use theCochran formula. Data processing method uses multiple linear regression method with the help of SPSS (Product Solutionand Service Statistics) version 22. The test results prove that the facility has a significant and positive effect on customersatisfaction at a significance level of 0,000 <0.05, the quality of service has a significant and positive effect on satisfactionconsumers at a significance value of 0,000 <0.05 and at the same time facilities and service quality have a significant andpositive effect on customer satisfaction with a significance value of 0,000 <0.05.